Educational Innovation in the Amazonian Context: An Educational Approach to Virtual Education at the Universidad de la Amazonia - Váquiro – Plazas, Yeison Andrés; Castro – Lozada , Jaime Andrés; Jaramillo – Morales , César Omar; Váquiro – Plazas , Díber Albeiro (Universidad Francisco de Paula Santander, 2023)
The results of the Feasibility Study and Market Research for the creation of the Master's Degree in Educational Innovation virtual modality at the Universidad de la Amazonia are presented. Applying a probabilistic sampling and the pertinent instruments, the level of perception and acceptance in the selected sample was captured. The objective of the study was to identify the existing potential demand. This study was a descriptive cross-sectional study, developed under the mixed method. The results showed a high acceptance by the surveyed population and in accordance with the needs identified from the Amazonian territory.